The acute toxicity of the metaldehyde on the climbing perch - Mohamad Ismail, Syamimi Wahida; Dahalan, Farrah Aini; Zakaria, Ammar; Mad Shakaff, Ali Yeon; Ahmad, Siti Aqlima; Abd Shukor, Mohd Yunus; Sabullah, Mohd Khalizan; Abdul Khalil, Khalilah; Ab Jalil, Mohd Faizal (EDP Sciences, 2018)
In Asia, Climbing perch (Anabas testudineus) is commonly found in paddy fields and irrigation systems. Due to its habitat, Climbing perch is exposed to toxic pesticides used in paddy fields such as metaldehyde which is one of the most widely used molluscicide. This study aims to determine the acute toxicity Lethal Concentration50 (LC50) of metaldehyde and its effect on the behaviour and physical changes of the Climbing perch. The fish mortality responses to six different metaldehyde concentrations ranging from 180 to 330 mg/L were investigated. The 96-h LC50 values were determined and analysed using three different analysis methods which is arithmetic, logarithmic and probit graphic. The LC50 values obtained in this study were 239, 234 and 232 mg/L, respectively. After 96-h of exposure to metaldehyde, the fish showed a series of abnormal behavioural response in all cases: imbalance position, and restlessness of movement. The LC50 values show that metaldehyde is moderately toxic to the Climbing perch indicating that metaldehyde is not destructive to Climbing perch. However, long term exposure of aquatic organisms to the metaldehyde means a continuous health risk for the fish population as they are more vulnerable and it is on high risk for human to consume this toxicated fishes.